PENANGANAN COVID-19 DALAM PERSPEKTIF PENTAHELIX (STUDI KASUS DI KOTA PEKALONGAN) - Latif, Rr. Vita Nur; Isrofah, Isrofah; Priharwanti, Ardiana (BAPPEDA Kota Pekalongan, 2020)
The development of the pandemic in Pekalongan from the beginning of March 2020 to today is a total of 69 confirmed positive cases, with details: 8 people were treated, 12 people were isolated independently, 35 people recovered, 7 people died. To be able to reduce the prevalence rate of cases which continues to show a significant increase, a synergistic control scenario is needed with the optimization of the role of the pentahelix (government, society, academia, private sector, health service providers). Methods. This study used an exploratory research design with a qualitative approach. The research subjects which contained elements of the pentahelix (government, society, academics, private sector, health service providers). Result. Based on the research findings on the role and optimization of pentahelix, all elements of pentahelix (government, academics, society, media and the private sector) have all taken roles even though there are several implementation obstacles in the field, especially in the profile and level of community compliance, particularly in public facilities such as traditional markets, pilgrimages. sapuro, religious activities and others. Keywords: Pentahelix, Covid-19